Upregulation of the WNK4 Signaling Pathway Inhibits Epithelial Sodium Channels of Mouse Tracheal Epithelial Cells After Influenza A Infection - Hou, Yapeng; Cui, Yong; Zhou, Zhiyu; Liu, Hongfei; Zhang, Honglei; Ding, Yan; Nie, Hongguang; Ji, Hong-Long (Frontiers in Pharmacology, 2019)
Influenza virus has a significant impact on the respiratory system. The mechanism of how influenza virus impairs the fluid transport in airway is not fully understood. We examined its effects on epithelial sodium channels (ENaC), which are very important for water and salt transport in the respiratory system. We focused on the impacts of influenza virus on ENaC activity in mouse tracheal epithelial cells (MTECs) and applied Ussing chamber apparatus for recording the short-circuit currents in primary cultured MTECs. Expressions of α and γ-ENaC were measured at the protein and mRNA levels by western blot and quantitative real-time polymerase chain reaction, respectively. Roles of the with-no-lysine-kinase-4 (WNK4) pathway were considered in participating influenza virus-involved ENaC regulation by using siRNA to knockdown WNK4 and the physical properties of airway surface liquid (ASL) were detected by confocal microscopy. Our results showed that influenza virus reduced ENaC activity, and the expressions of α and γ-ENaC were decreased at the protein and mRNA levels, respectively. WNK4 expression increased time-dependently at the protein level after influenza virus infection, while knockdown of WNK4 rescued the impact of influenza virus on ENaC and ASL height increased obviously after MTECs were treated with influenza virus. Taken together, these results suggest that influenza virus causes the changes of biophysical profile in the airway by altering the ENaC activity at least partly via facilitating the expression of WNK4.